Effect of phosphorus and bioinoculants and their residual effect on succeeding chickpea (Cicer arietinum) - KUMAWAT, NARENDRA; YADAV, R K; SINGH, MAHENDER; DUDWE, T S; TOMAR, I S (The Indian Journal of Agricultural Sciences, 2020)
A field experiments were conducted during kharif and rabi 2016–17 and 2017–18 at ZARS, Jhabua to study the effect of phosphorus and bioinoculants on growth attributes, yields, nutrient uptake and economics in maize - chickpea cropping system. Among the treatments, significantly higher growth and yield parameters of maize were recorded with the application of 60 kg P2O5/ha + NPK consortia as compared to other treatments. The highest grain yield (54.62 q/ha), stover yield (52.63 q/ha), biological yield (106.58 q/ha) were obtained under 60 kg P2O5/ha + NPK consortia which was at par to each other and significantly superior to control, PSB I, PSB II and NPK consortia. This treatment also observed the highest total N, P and K uptake by grain and stover. The residual study of phosphorus and bioinoculants on succeeding chickpea was found to have significant effect on growth and yield attributes. Among the various treatments, maximum seed yield (24.04 q/ha), and biological yield (60.69 q/ha) were observed under 60 kg P2O5/ha + NPK consortia. Similarly, the highest total uptake of N, P and K were recorded with the application of 60 kg P2O5/ha + NPK consortia. Treatment receiving 60 kg P2O5/ha + NPK consortia realized the maximum gross return (×103 204.34 `/ha), net return (×103 157.08 `/ha) and B:C ratio (3.32) as compared to other treatments.